Theoretical and Experimental Study on the Performance of Photovoltaic using Porous Media Cooling under Indoor Condition - Ismail Masalha; Siti Ujila binti Masuri; Omar Badran; Mohd Khairol Anuar bin Mohd Ariffin; Abd Rahim Abi Talib; Fadi Alfaqs (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
This paper presents the theoretical and experimental investigation on performance of a photovoltaic (PV) panel cooled by porous media under indoor condition. Porous media offer a large exterior surface area and a high fluid permeability, making them ideal for PV cells cooling. The photovoltaic panel was cooled using 5 cm thick cooling channel filled with porous media (gravel). Several sizes of porosity (0.35, 0.4, 0.48, and 0.5) at different volume flow rates (1, 1.5, 2, 3, and 4 L/min) were tested to obtain the best cooling process. The theoretical analysis was performed at the optimum case found experimentally, which has a porosity of 0.35 and a volume flow rate of 2 L/min, to test various experimental results of the PV hot surface temperature, related power output, efficiency and I-V characteristic curve. The enhancement obtained in PV power output and efficiency is compared against the case without cooling and the case using water alone without porous media. Results showed that cooling using small size porous media and moderate flow rate is more efficient which reduces the average PV hot surface temperature of about 55.87% and increases the efficiency by 2.13% than uncooled PV. The optimum case reduced the PV hot surface temperature to 38.7°C, and increased the power output to 19 W, efficiency to 6.26%, and the open voltage to 22.77 V. The results showed that the presence of small porous media of 0.35 in the PV cooling process displayed the maximum effectiveness compared to the other two scenarios, because the heat loss from PV surface through porous media layer have developed a homogenous heat diffusion removed much quicker at high flow rate (2 L/min). A good agreement was obtained between experimental and theoretical results for different cases with a standard deviation from 3.2% to 5.6%.